Strengthening Resilience: Parent Experiences in Developing their Children Executive Function Skills - Sangsuk, Nisachon; Saengkaew, Rarin; Klankaradi, Kuephan; Wongkruasorn, Watcharawan (Jurnal Keperawatan Soedirman, 2024)
Executive functions (EF) play a key role in child development. However, Thai parents’ knowledge and practice skills for their children’s EF are still limited. This study aimed to explore the lived experiences of Thai parents in developing their children’s EF skills in a semi-rural sociocultural context. The theme pattern was interpreted using the Heideggerian hermeneutic phenomenological approach, and the themes were reflected in Van Manen’s fundamental existential themes of the life world. As many as 16 parents were selected using the purposive sampling method. Semi-structured interviews were conducted. The results of this study revealed seven themes: 1) strong resilience, self-confidence, and responsibilities; 2) challenges in handling misbehaving family members and children with poor self-control; 3) living in a natural and peaceful environment; 4) staying away from terrible things; 5) practicing time management; 6) trying to use the mobile phone safely; and 7) organizing belongings and toys. In conclusion, nurses can help parents to increase their children’s EF skills by strengthening parents’ resilience, self-confidence, and responsibilities; supporting parents and co-parents to deal with terrible situations; time management; and preparing a safe, green, and natural environment for children to develop their EF skills.